Fundamental virology - Knipe, David M. (Lippincott Williams & Wilkins, 2001)
This volume brings together the basic science chapters from the two-volume Fourth Edition of Fields Virology. These 37 chapters comprise a comprehensive text and reference on the concepts and research techniques of contemporary virology and the biochemistry, molecular biology, and replication of all viruses